MARIA DA PENHA LAW: A LEGAL-SOCIAL ANALYSIS OF THE (IN)EFFECTIVENESS OF ´PROTECTION MEASURES APPLICABLE AGAINST DOMESTIC VIOLENCE (REMUNOM, 2024)
The purpose of this scientific research is the legal-social analysis of the (in)effectiveness of protection measures for victims of the crime of domestic violence, provided for in Law No. 11,340/06 (Maria da Penha Law). Domestic violence is a crime that is constantly growing in Brazilian society, with the public authorities not being able to control it through conventional public protection measures, nor through the special measures provided for in the law above. Therefore, this article becomes essential in the search to innovate, improve and, finally, protect definitively and/or in the long term any victims of this criminal conduct.